COVID-19 associated atrial fibrillation: Incidence, putative mechanisms and potential clinical implications. (October 2020) - Gawałko, Monika; Kapłon-Cieślicka, Agnieszka; Hohl, Mathias; Dobrev, Dobromir; Linz, Dominik
Abstract: Coronavirus disease 2019 (COVID-19) is a novel, highly transmittable and severe strain disease, which has rapidly spread worldwide. Despite epidemiological evidence linking COVID-19 with cardiovascular diseases, little is known about whether and how COVID-19 influences atrial fibrillation (AF), the most prevalent arrhythmia in clinical practice. Here, we review the available evidence for prevalence and incidence of AF in patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and discuss disease management approaches and potential treatment options for COVID-19 infected AF patients.